MAPPING OF PELAGIC FISHING POTENTIALS USING SINGLE IMAGE EDGE DETECTION (SIED) AND TEMPERATURE GRADIENT ANALYSIS (TGA) IN THE WATERS OF PADANG CITY - Rahmad Triadi Akbar; Sri Kandi Putri (International Remote Sensing Applied Journal, 2020)
Padang City waters are one of the waters that have very promising potential for fishermen. This study aims to obtain potential areas for catching large pelagic fish which are analyzed using fashionable image data of chlorophyll a and SST. This research was carried out in November 2021. This research covered the period June, July and August, on June 9 potential zones for large pelagic fish were scattered, based on the distribution of potential large pelagic fish zones a distance of beat tween 1,000 meters to 5,000 resulted in 5 zones of potenzones for large pelagic fish and a distance of 1,000 meters to 10,000 or sea II produces 4 zones indicating the potential for large pelagic fish. In July the potential zone for large pelagic fish increased by 14 potential zones for large pelagic fish from a distance of 5. As a result, the distribution of sea surface temperature increases every month and the distribution of chlorophyll tends to crease. Based on the results of the interpolation of the potential for large pelagic fish, August is a month that has the potential for large pelagic fish catching zones, in the distribution of potential fish zones in the waters of Padang City, the average sea depth is between 10 meters and 50 meters. Based on tests of the accuracy of the distribution of fishing vessels in the waters of the City of Padang, only 5,000 meters from the shoreline, this has resulted in fewer fisherfewerbeing able to explore the potential spread across the waters of the City of Padang because there are no ships with engines with tonnage or wide cruising to be able to explore existing the potential.